DKWS: A Distributed System for Keyword Search on Massive Graphs - Jiang, Jiaxin; Choi, Byron; Huang, Xin; Xu, Jianliang; Bhowmick, Sourav S (IEEE transactions on knowledge and data engineering, 2024)
Due to the unstructuredness and the lack of schemas of graphs, such as knowledge graphs, social networks, and RDF graphs, keyword search for querying such graphs has been proposed. As graphs have become voluminous, large-scale distributed processing has attracted much interest from the database research community. While there have been several distributed systems, distributed querying techniques for keyword search are still limited. This paper proposes a novel distributed keyword search system called \mathsf {DKWS} DKWS<inline-graphic xlink:href="jiang-ieq1-3313726.gif"/> . First, we present a monotonic property with keyword search algorithms that guarantees correct parallelization. Second, we present a keyword search algorithm as monotonic backward and forward search phases. Moreover, we propose new tight bounds for pruning nodes being searched. Third, we propose a notify-push paradigm and \mathsf {PINE} PINE<inline-graphic xlink:href="jiang-ieq2-3313726.gif"/> programming model of \mathsf {DKWS} DKWS<inline-graphic xlink:href="jiang-ieq3-3313726.gif"/> . The notify-push paradigm allows asynchronously exchanging the upper bounds of matches across the workers and the coordinator in \mathsf {DKWS} DKWS<inline-graphic xlink:href="jiang-ieq4-3313726.gif"/> . The \mathsf {PINE} PINE<inline-graphic xlink:href="jiang-ieq5-3313726.gif"/> programming model naturally fits keyword search algorithms, as they have distinguished phases, to allow preemptive searches to mitigate staleness in a distributed system. Finally, we investigate the performance and effectiveness of \mathsf {DKWS} DKWS<inline-graphic xlink:href="jiang-ieq6-3313726.gif"/> through experiments using real-world datasets. We find that \mathsf {DKWS} DKWS<inline-graphic xlink:href="jiang-ieq7-3313726.gif"/> is up to two orders of magnitude faster than related techniques, and its communication costs are 7.6 times smaller than those of other techniques.